Reasons for not collecting health insurance premiums and ways to facilitate its collection: a qualitative study - Hakimeh Mostafavi; Rouholah Gholikhani; Alireza Olyaeemanesh; Amirhossein Takian (Payesh)
Objective(s): The increasing growth of treatment costs indicates the necessity of insurance coverage of the population. The continuance of this coverage requires sufficient financial resources. One of these financial sources is the insurance premium. Failure to pay it timely causes problems for the insurer and the insured. This study seeks to identify the causes of non-payment of insurance premiums by the health insurance organization and provide solutions to solve them. Methods: This qualitative study was conducted through semi-structured interviews and focused discussion sessions. The snowball method was used to identify the interviewees. The interviews continued until data saturation was reached. To analyze the data, the conventional content analysis approach was used based on the method suggested by Granheim and Lundman. Results: Based on the findings of the study, the causes of non-payment of insurance premiums include non-payment/late payment of insurance premiums by the government, non-payment/late payment of insurance premiums by the executive body, unscientific budgeting, budget deficit, non-compliance with the law, and allocation It is a quarterly budget. By using a set of legal and non-legal solutions, it is possible to facilitate the timely collection of insurance premiums. Conclusion: Although the government is the main provider of the organization's insurance premium, the organization as a key institution should seek to find solutions to solve its financial problems. Active management of the organization's expenses, taking advantage of new methods of income generation, and attracting the support of charity organizations are suitable solutions to solve the relative financial problems of the organization.